Comparative Analysis in the Structure of the Expenditure of the „Central Government” Subsector of the EU-26 and Bulgaria - Tsoklinova, Maya (Research Papers, 2024)
The periodic study of the expenditure of the “Central Government” subsector by functions of COFOG allows revealing the state priorities in the provision of public goods during different time period, as well as the possibilities for implementing effective redistributive policies. The main purpose of the report is to examine the differences in the structure of the expenditure of the “Central Government” subsector by the functions of COFOG between the EU-26 and Bulgaria for the period 1998 – 2020 and on this basis to reveal opportunities for redistribution that is more effective and increase of public welfare in Bulgaria.
Keywords: Functions of COFOG; Government expenditure; Dependencies; Structure; Redistributive policies